The woman who rides like a man - Pierce, Tamora (New York : Atheneum, 1986)
On her first tour as a knight errant, Alanna assumes a position of influence with a fierce desert tribe, makes some changes in the role of women in the society, and continues her own emotional development.
"An Argo book."
Keywords: Alanna, -- of Trebond -- (Fictitious character) -- Fiction; Knights and knighthood -- Fiction; Sex role -- Fiction; Magic -- Fiction; Fantasy fiction; Young adult fiction